CBCT Diagnosis of Palatogingival Groove in the Maxillary Central Incisor: A Case-Based Review - Fischborn, Amanda Regina; Pedroso, Caique Mariano; Rigo, Natália Mariane; de Oliveira, Fabio Brasil; Zavarez, Larissa Balbo; Claudino, Marcela; Nobre Franco, Gilson Cesar (Odovtos - International Journal of Dental Sciences, 2023)
The palato-gingival groove (PGG) is a variation of normality characterized by a fissure along the root of the anterior-superior teeth, in which late detection could result in clinical-related complications. A 16-year-old female underwent a cone-beam computed tomography (CBCT) for an orthodontic evaluation to assess the presence and position of impacted maxillary canines. CBCT revealed the presence of a PGG in the upper right central incisor. Clinically, a sulcus was detected in the cingulum region, accompanied by gingival inflammation. In tomographic sections, the extension of the sulcus from the cingulum to the apical third was observed. A periodontal approach was performed, followed by an 18-month follow-up. At this follow-up, no clinical evidence of gingival inflammation was observed, characterizing a favourable prognosis. PGG is an unusual variation that affects maxillary anterior incisors. The early detection of this sulcus, performed only by CBCT, is associated with a favourable prognosis.